2012
DOI: 10.1039/c1cc15597k
|View full text |Cite
|
Sign up to set email alerts
|

Carbon/metal nanotubes with tailored order and configuration by direct carbonization of inverse block copolymer micelles inside nanoporous alumina

Abstract: Carbonaceous nanotubes decorated with metal nanoparticles were obtained by heating inverse block copolymer micelles loaded with metal precursors inside nanoporous alumina. Simple changes in the applied temperature profile allowed tailoring of the wall morphology of the nanotubes and the spatial arrangement of the metal nanoparticles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Block copolymers (BCPs) have been shown to be simultaneously suitable as carbon precursors and as soft templates in the design of creative mesoporous architectures. Commercially available structure-directing agents, e.g., amphiphilic poly­(ethylene oxide)–poly­(propylene oxide)–poly­(ethylene oxide) triblock copolymer Pluronic P123, have been widely used in the synthesis of mesostructured TiO 2 ( m TiO 2 ) . Alternatively, following a simple one-step carbonization procedure, Pluronic P123 has been simultaneously reported by some of us in the synthesis of carbon-doped m TiO 2 . …”
Section: Introductionmentioning
confidence: 99%
“…Block copolymers (BCPs) have been shown to be simultaneously suitable as carbon precursors and as soft templates in the design of creative mesoporous architectures. Commercially available structure-directing agents, e.g., amphiphilic poly­(ethylene oxide)–poly­(propylene oxide)–poly­(ethylene oxide) triblock copolymer Pluronic P123, have been widely used in the synthesis of mesostructured TiO 2 ( m TiO 2 ) . Alternatively, following a simple one-step carbonization procedure, Pluronic P123 has been simultaneously reported by some of us in the synthesis of carbon-doped m TiO 2 . …”
Section: Introductionmentioning
confidence: 99%
“…1d) of the carbonaceous nanotubes. 15 The EDS elemental mapping of C, N and O atoms, which is integrated with the TEM image of the same region, illustrates a homogeneous distribution of heteroelements in the N-PANn-1000 nanotube (see Fig. 1e).…”
mentioning
confidence: 99%
“…Anodic alumina oxide (AAO) has been used to fabricate aligned macroporous polymer nanotube arrays 14 and macroporous carbonaceous nanotubes decorated with metal nanoparticles by heating inverse block copolymer micelles loaded with metal precursors inside nanoporous alumina. 15 In this communication, we envision that N-doped 1D macroporous carbonaceous arrays can be fabricated from the AAO template. The excellent electron-rich element doping effect and prompt mass transfer in the macropores should combine together in the novel structure, and thus result in a high efficient ORR catalyst.…”
mentioning
confidence: 99%
“…The mixture of PSMA and Jeffamine-PSMA was not soluble in the LE components (SM and SH in Table 1) and did not undergo gelation regardless of the UV dosage. Although several authors have reported that polystyrene can be UV-cross- linked, 43,44 the cross-linking efficiency of polystyrene appears to be very low in diluted and/or heterogeneous systems. These behaviors suggest the importance of the p-hydroxystyrene-based cross-linker for the efficient formation of GPE.…”
Section: Resultsmentioning
confidence: 99%